PENERAPAN PENDEKATAN CTL UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 013 BASILAM BARU - Alpusari, Mahmud Alpusari Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. The problem aims to improve student learning outcomes through the implementation of IPA contextual teaching and learning approach in the fourth grade students of SDN 013 Basilam Baru 2103/2014 school year the number of students 12 people, 4 boys and 8 girls. The design of this study is Classroom Action Research (CAR). The parameters measured were the result of student learning, teacher activity and student activity. While the research instrument used is the observation sheet items and teacher activity and student activity. Based on the results of the analysis of data from the discussion, the average student learning outcomes in the first cycle increased from an average of 6.63 as the initial data of 59 becomes 65.83. Average student learning outcomes in second cycle increased by 15.83 points from 65.83 into 81.66. The percentage of all teachers in the first cycle was 85.71% with both categories increased in the second cycle becomes 92.42% with very good category. The percentage of student activity in the first cycle was 75% with both categories increased in the second cycle becomes 92.85% with very good category. It can be concluded that the hypothesis is that if applied contextual teaching and learning approach can improve the results of the fourth grade students learn science SDN 013 Basilam Baru. Keywords: contextual approach and the application of learning, learning outcomes SAIN